Life cycle costing of MRI machine at a tertiary care teaching hospital - Sahu, Anupam; Vikas, H; Sharma, Nishant (Indian Journal of Radiology and Imaging, 2020)
Background: Life cycle costing (LCC) is an excellent decision-making tool that can assist a hospital administrator in seeking more cost-effective decisions to select the best course of action. LCC can be defined as “an economic assessment of competing design alternatives, considering all significant costs of ownership over the economic life of each alternative, expressed in equivalent rupees. Aim: To determine the LCC of magnetic resonance imaging (MRI) machine at a tertiary care teaching hospital. Settings and Design: A descriptive, observational study in MRI scan center of a tertiary care teaching hospital. Materials and Methods: LCC analysis (LCCA) was performed to ensure total cost visibility for the entire life span of the MRI scan equipment, which was assumed to be 10 years. Statistical Analysis: Data were analyzed using MS Excel. Results and Conclusions: The total cost per MRI scan was calculated to be Rs. 2944. It was estimated that the MRI scan center would reach the break-even point by the end of the third year.
Keywords: Break-even point; cost effectiveness; life cycle cost; MRI Centre; MRI costing